Study on Some Hydroxyaryltellurium(IV) Trichlorides Catalyzed Knoevenagel Reactions - Garg, Sapana; Narwal, J.K.; Verma, K.K. (Asian Journal of Chemistry, 2012)
Hydroxyaryltellurium trichlorides, R'TeCl3 (p-hydroxyphenyl and 3-methyl-4-hydroxyphenyl) have been prepared by condensation of tellurium tetrachloride with phenol or o-cresol respectively. These hydroxyaryltellurium trichlorides have been investigated as catalysts in Knoevenagel reactions between non-enolizable aldehydes and active methylene compounds to yield the corresponding olefinic products. This paper reports the reaction of ethylcyanoacetate, malononitrile and cyanoacetamide with aromatic aldehydes, ArCHO (Ar is C6H5, 4-ClC6H4, 4-CH3OC6H4 and C6H5-CH=CH). The products are obtained in excellent yield and high purity and have been identified by comparison of their properties with those of authentic samples.